Pengaruh Pembinaan Rohani terhadap Kesehatan Mental Anggota: Pembinaan Rohani dan Mental Polri di Polrestabes Bandung - Ghofur Rurohim; Miharja, Sugandi (Assertive: Islamic Counseling Journal, 2024)
Police officers can experience mental health problems due to the pressure and high demands of their work, so spiritual development is needed for police officers. This research aims to measure the influence of spiritual coaching on the mental health of National Police members in spiritual and mental coaching at the Bandung Police. This research was conducted using quantitative descriptive methods. The results of data processing using the SPSS version 29 for Windows application showed that 15 respondents were members of the Bandung Police, represented by Bhabinkamtibmas within the Bandung Police, using a sample of 10% of the total population. The results of the research in the form of a simple linear regression test produce research significance of 0.001 < 0.05, which states that there is a positive influence between spiritual formation and mental health. With an R square or coefficient of determination of 0.750, it shows that there is an influence of spiritual formation on mental health with a percentage level of 75%. So, spiritual formation has an influence on mental health.   Anggota Polri bisa memiliki permasalahan kesehatan mental karena adanya tekanan dan tuntutan pekerjaan yang tinggi, maka diperlukan pembinaan rohani untuk anggota Polisi. Penelitian ini bertujuan untuk mengukur pengaruh pembinaan rohani terhadap kesehatan mental anggota Polri dalam pembinaan rohani dan mental di Polrestabes Bandung. Penelitian dilakukan dengan kuantitatif deskriptif. Hasil pengolahan data menggunakan bantuan aplikasi SPSS versi 29 for Windows, sebanyak 15 responden personil anggota Polrestabes Bandung yang diwakilkan kepada Bhabinkamtibmas lingkup Polrestabes Bandung dengan menggunakan sampel dari 10% total populasi. Hasil penelitian adalah uji regresi linier sederhana bahwa hasil signifikansi penelitian 0,001 < 0,05 yang menyatakan bahwa terdapat pengaruh positif antara pembinaan rohani dan kesehatan mental. Dengan R square atau koefisien determinasi sebesar 0,750, sehingga menunjukkan pengaruh Pembinaan Rohani terhadap kesehatan mental dengan tingkat persentasi 75%. Maka, pembinaan rohani memiliki pengaruh pada kesehatan mental.